Effect of dexmedetomidine sedation on swallowing reflex: A pilot study - Takuro Sanuki; Gaku Mishima; Takao Ayuse (Elsevier, 2020)
Background/purpose: Swallowing reflex depression during dental treatment or oral surgery may cause water to enter the lower respiratory tract, leading to coughing, thus hindering these procedures. Based on the hypothesis that dexmedetomidine (DEX) sedation may depress swallowing reflex, we aimed to characterize its effects on swallowing reflex and elucidate the affected functions. Materials and methods: Swallowing reflex was induced in 9 young healthy male volunteers using a 5 mL-distilled water bolus injection over 3 s through a polyethylene catheter 3 times, both under wakefulness and DEX sedation. Swallowing EMG burst duration, pre-swallow EMG activity value, swallowing EMG burst peak value, latency time, and swallowing reflex timing in relation to the respiratory cycle were analyzed. Results: The EMG burst duration was significantly prolonged with DEX sedation [206.9 ± 90.3% (1.20 ± 0.98 s)] compared to that with wakefulness [100 ± 00% (0.53 ± 0.28 s), P = 0.007]. No significant differences in the pre-swallow EMG activity value (P = 0.343), swallowing EMG burst peak value (P = 0.218), and latency times were apparent between wakefulness and DEX sedation (P = 0.793). Distributions of timing of the swallows in relation to the respiratory cycle did not significantly differ between the two conditions (P = 0.860). Conclusion: Our data demonstrate that DEX sedation carries a potential risk of aspiration due to swallowing reflex depression during elevation of the larynx; therefore, suctioning of water and saliva should be rigorously performed. However, peripheral muscle contraction of the submental muscle complex, neural organization function, and timing of the swallowing reflex in relation to the respiratory cycle are not affected.